2021
DOI: 10.3390/pathogens10121583
|View full text |Cite
|
Sign up to set email alerts
|

Host Range, Biology, and Species Specificity of Seven-Segmented Influenza Viruses—A Comparative Review on Influenza C and D

Abstract: Other than genome structure, influenza C (ICV), and D (IDV) viruses with seven-segmented genomes are biologically different from the eight-segmented influenza A (IAV), and B (IBV) viruses concerning the presence of hemagglutinin–esterase fusion protein, which combines the function of hemagglutinin and neuraminidase responsible for receptor-binding, fusion, and receptor-destroying enzymatic activities, respectively. Whereas ICV with humans as primary hosts emerged nearly 74 years ago, IDV, a distant relative of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 235 publications
(301 reference statements)
0
10
0
Order By: Relevance
“…Influenza C virus was first isolated from humans in 1947 [ 36 ] and is widely distributed throughout the world. It infects humans, dogs, swine, camels, horses, and bovines, although humans are the primary host [ 37 ]. Influenza C virus causes relatively mild respiratory illness; however, it can cause bronchitis and pneumonia, particularly in children younger than 2 years or patients with underlying illnesses [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza C virus was first isolated from humans in 1947 [ 36 ] and is widely distributed throughout the world. It infects humans, dogs, swine, camels, horses, and bovines, although humans are the primary host [ 37 ]. Influenza C virus causes relatively mild respiratory illness; however, it can cause bronchitis and pneumonia, particularly in children younger than 2 years or patients with underlying illnesses [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the virus has been detected in bovines in several countries including USA, Mexico, France, Japan, Italy, China, and Ireland [ 43 , 44 , 45 , 46 , 47 , 48 ]. Global serological studies have shown that influenza D virus has a broad host range, including humans, swine, sheep, goats, camels, horses, and bovines, although the primary host of influenza D virus is bovines [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICV and IDV also bind to a chemically different receptor than IBV or IAV [ 103 , 104 , 105 ]. Wider natural host ranges for ICV and IDV compared to IBV have been described [ 106 ]. Unfortunately, little is known mechanistically about the host restriction factors for ICV or IDV.…”
Section: Summary and Future Research Directionsmentioning
confidence: 99%
“…Both ICV and IDV utilize the same receptor determinant to enter the host cell, however both viruses have distinct host reservoirs; human for ICV and bovine for IDV (8,9,12,(16)(17)(18). Nonetheless, despite the common receptor determinant usage, IDV has shown to have a broader host tropism compared to ICV, suggesting that other factors might play a dominant role in cross-species virus transmission (7).…”
Section: Distinct Replication Kinetics For Icv and Idv In Aec Culture...mentioning
confidence: 99%
“…Interestingly, both the ICV and IDV HEF glycoproteins can bind to the luminal surface of human, porcine, and bovine respiratory epithelium, although both viruses noticeably differ in their respective host tropism (7). ICV is predominantly a human pathogen, causing respiratory diseases in infants and children, and has sporadically been associated with respiratory infections in swine and cattle (8)(9)(10)(11). In contrast, IDV exhibits an intrinsic broad host tropism among different livestock (12)(13)(14)(15), with cattle as the main host reservoir (12,(16)(17)(18), and was shown to have a zoonotic potential (19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%